Developing of Articulate Storyline of Economic Learning Media to Improve Student Learning Outcomes at SMA Negeri 1 Deli Tua - Ritonga, Marito; Maipita, Indra; Tambunan, Khairuddin E. (Cakrawala: Jurnal Pendidikan, 2022)
This study aimed to develop and implement Articulate Storyline economic learning media to improve economic learning outcomes for class XI students of SMA Negeri 1 Deli Tua. This research is development research (R&D) with the ADDIE method. This research was conducted at SMA Negeri 1 Deli Tua, with a population of all students of class XI IPS. The results of this study are based on the assessment carried out by validation experts and user responses, the average percentage of assessment is 92% "Very Eligible" so it is concluded that the Articulate Storyline economic learning media developed meets the eligibility requirements (valid) to be used as an economics learning medium for class XI Social Sciences. The average learning outcomes of the experimental class were 88.00 and the control class 69.69. Obtaining independent t-test 9.623 > 1.9955 with sig. 0.00 < 0.05. So it can be concluded that the storyline articulation of economic learning media that was developed was effectively used to help students improve economic learning outcomes for class XI IPS SMA Negeri 1 Deli Tua.